Phospholipase C5 (NPC5) is involved in galactolipid accumulation during phosphate limitation in leaves of Arabidopsis - Gaude, Nicole; Nakamura, Yuki; Scheible, Wolf-Rüdiger; Ohta, Hiroyuki; Dörmann, Peter (The Plant journal : for cell and molecular biology, 2008)
The replacement of phospholipids by galacto- and sulfolipids in plant membranes represents an important adaptive process for growth on phosphate-limiting soils. Gene expression and lipid analyses revealed that the MYB transcription factor PHR1 that has been previously shown to regulate phosphate responses is not a major factor controlling membrane lipid changes. Candidate genes for phospholipid degradation were selected based on induction of expression during phosphate deprivation. Lipid measurements in the corresponding Arabidopsis mutants revealed that the non-specific phospholipase C5 (NPC5) is required for normal accumulation of digalactosyldiacylglycerol (DGDG) during phosphate limitation in leaves. The growth and DGDG content of a double mutant npc5 pho1 (between npc5 and the phosphate-deficient pho1 mutant) are reduced compared to parental lines. The amount of DGDG increases from approximately 15 mol% to 22 mol% in npc5, compared to 28 mol% in wild-type, indicating that NPC5 is responsible for approximately 50% of the DGDG synthesized during phosphate limitation in leaves. Expression in Escherichia coli revealed that NPC5 shows phospholipase C activity on phosphatidylcholine and phosphatidylethanolamine. A double mutant of npc5 and pldζ2 (carrying a mutation in the phospholipase Dζ2 gene) was generated. Lipid measurements in npc5 pldζ2 indicated that the contribution of PLDζ2 to DGDG production in leaves is negligible. In contrast to the chloroplast envelope localization of galactolipid synthesis enzymes, NPC5 localizes to the cytosol, suggesting that, during phosphate limitation, soluble NPC5 associates with membranes where it contributes to the conversion of phospholipids to diacylglycerol, the substrate for galactolipid synthesis.